Collaboration in Inclusive Education - BHARTI (THE PRIMARY TEACHER, 2014)
The rapidly changing education scenario in India facilitated by implementation of Right to Education Act-2009 is making Indian classroom more and more diverse in terms of students needs. More and more classrooms are now witnessing the presence of children with disabilities. As a result of efforts under Sarva Shiksha Abhiyaan (SSA), enrolment and retention of children with special needs up to elementary level has also increased there by adding to the existing diversity in the classroom. Managing the teaching-learning of children with special needs within the same classroom along with their non-disabled peers is becoming a challenge for the regular teachers due to a number of reasons. The foremost of them is the lack of training in inclusive education practices. Realising this as a challenge the various policies and programmes of Government of India like SSA and Rashtriya Madhyamik Shiksha Abhiyaan (RMSA) have attempted to meet this challenge by organising a large number of in-service teacher training programmes and also by recruiting special education teachers. The efforts of the Government though effective, however are just like a drop in the ocean due to the huge number of regular teachers as well as identified children with disabilities